Effectiveness of Using Case Simulation to Develop Communication Skills of Nursing Students in English Language Learning - Maria Theresia Priyastuti (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
This study aimed to examine the effectiveness of case simulation in improving nursing students’ communication skills in English language learning. Using a quantitative descriptive design, 200 purposively selected S1 and D3 Nursing students at STIKes Elisabeth Semarang participated in case simulations integrated into an English for Nursing course. Data were collected using a questionnaire based on the Communication Skills Assessment Tool (CSAT) and a performance rubric assessing verbal clarity, medical terminology use, patient response, non-verbal communication, professional attitude, teamwork, and empathy. The results showed that empathy, non-verbal communication, and professional attitude received the highest mean scores, while medical terminology use was the lowest. The instrument demonstrated excellent reliability (Cronbach’s Alpha = 0.966). Significant positive correlations were found between students’ perceptions of simulation effectiveness and their assessed communication skills, particularly in patient response and verbal clarity. The findings indicate that case simulation is an effective approach for integrating technical and interpersonal communication skills and enhancing students’ readiness for real-world multicultural healthcare interactions. However, improvements are still needed in verbal clarity and medical terminology, suggesting the importance of structured instruction, systematic feedback, vocabulary-focused modules, and teamwork-oriented learning activities. Limitations of the study include reliance on self-reported data, the absence of observer-based teamwork assessment, and its non-experimental design. Future research is recommended to use mixed-method and longitudinal approaches to better evaluate skill transfer into clinical practice.